2022
DOI: 10.18778/0867-5856.32.1.07
|View full text |Cite
|
Sign up to set email alerts
|

Employee performance analysis of Paul Bakery Restaurant in Jakarta during the COVID-19 pandemic by measuring leadership, motivation and compensation through job satisfaction

Abstract: The purpose of this study is to analyze the influence of leadership, compensation and motivation, by using job satisfaction as an intervening variable, on employee performance during a crisis in the context of a company in the restaurant service sector. A tiered linear regression with two models was used: Model 1 analyzed the influence of leadership, compensation and motivation on job satisfaction while Model 2 explored the impact of leadership, compensation, motivation and job satisfaction on performance. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
1
3
0
1
Order By: Relevance
“…Compensation also has a positive and significant effect on Job Satisfaction at JRP, which means that increasing or better Compensation at JRP will increase employee satisfaction. The results of this study are in line with research conducted by (Anshori & Nurwulandari, 2021) and (Budiono, 2022) which concluded that there is a positive and significant relationship between compensation and job satisfaction. So that compensation plays an important role in increasing employee satisfaction.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Compensation also has a positive and significant effect on Job Satisfaction at JRP, which means that increasing or better Compensation at JRP will increase employee satisfaction. The results of this study are in line with research conducted by (Anshori & Nurwulandari, 2021) and (Budiono, 2022) which concluded that there is a positive and significant relationship between compensation and job satisfaction. So that compensation plays an important role in increasing employee satisfaction.…”
Section: Discussionsupporting
confidence: 90%
“…According to (Indrasari et al, 2019) compensation factors include salary, benefits, bonuses, commissions, training, authority, responsibility, recognition of performance and a supportive work environment. Based on previous research conducted by (Anshori & Nurwulandari, 2021) and (Budiono, 2022) there is a positive and significant relationship between compensation and job satisfaction. However, the results of research conducted by (Efendi & Yusuf, 2021) found different conclusions, which showed positive results and an insignificant relationship between compensation and job satisfaction.…”
Section: A Introductionmentioning
confidence: 89%
“…The results of the Organization's adaptation to the situations and conditions can produce employee satisfaction who perceives that under these conditions, they can still carry out their activities in running the Organization so that their lives can survive in times of crisis. Motivation significantly influences Job Satisfaction (Alrawahi et al, 2020;Budiono, 2022). People motivated to carry out activities can give their best to get the expected results.…”
Section: Discussionmentioning
confidence: 99%
“…However, few companies can operate normally, both in terms of technical and revenue, as before the pandemic. Companies need to think of various ways so that the company's condition can be like before the crisis occurred (Budiono, 2022). Organisations in the food and beverage service industry, such as Starbucks coffee in Indonesia, especially Region VII, also experience similar things.…”
Section: Introductionmentioning
confidence: 99%